Kesiapan Masyarakat dalam Mengembangkan Pertanian 4.0 di Desa Cibodas Kecamatan Lembang - Indri Yuliantari Putri; Saraswati (UNISBA Press, 2023)
Abstract.Cibodas village is one of the locations that became agriculture 4.0 in Cijerokasi village, chosen by the ministry of agriculture for becoming a farming village in 2019. However, agriculture 4.0 farming still considers several factors such as community readiness and knowledge. Agriculture 4.0 will be feasible to develop and the community is ready to develop it. Therefore, it is necessary to know the readiness of the Cibodas Village community before development. This study aims to determine the feasibility of agriculture 4.0, identify the level of community readiness and determine strategies for developing agriculture 4.0. The research method used is mix methods. Data collection was carried out by interviews and questionnaires. Assessing feasibility using Cost Benefit Analysis, Feasibility R/C Ratio, Readiness assessment using Community Readiness Model, and determining strategies using SWOT. The results of the analysis show that agriculture 4.0 can be said to be feasible if farmers have 1Ha of land and are combined so that a period of 5 years according to the Net Present Value is obtained Rp 127,174,487.00 / year, with a Net B / C value of 10.63 meaning that every Rp 1,000 of capital will profit Rp 10,630, with a break-even point farmers managed to sell 12,633 kg of vegetables and the cost of investment will return in 1 year and 9 months. The Cibodas Village community is at readiness level 5, namely preparation, characterized by the availability of local resources and the availability of time so that the strategy is to build an integrated agricultural center in Cijarekso village as a development center for technology 4.0, installing agricultural equipment communally so that capital expenditures are minimal and building cooperatives as a forum for selling crops. Abstrak. Desa Cibodas merupakan salah satu lokasi yang menjadi pertanian 4.0 di kampung Cijerokasi, dipilih oleh kementerian pertanian karena menjadi desa tani tahun 2019. Namun usahatani pertanian 4.0 masih mempertimbangkan beberapa faktor seperti kesiapan dan pengetahuan masyarakat. Pertanian 4.0 apakah akan layak untuk dikembangkan dan masyarakat siap untuk mengembangkannya. Oleh karena itu perlu mengetahui kesiapan masyarakat Desa Cibodas sebelum pengembangan. Penelitian ini bertujuan mengetahui kelayakan pertanian 4.0, mengidentifikasi tingkat kesiapan masyarakat dan menentukan strategi mengembangkan pertanian 4.0. Metode penelitian yang digunakan adalah mix methods. Pengumpulan data dilakukan dengan wawancara dan kuisioner. Menilai kelayakan menggunakan Cost Benefit Analysis, Kelayakan R/C Ratio, Penilaian kesiapan menggunakan Community Readiness Model, dan menentukan strategi menggunakan SWOT. Hasil analisis menunjukan pertanian 4.0 bisa dikatakan layak jika petani memiliki lahan 1Ha dan digabung sehingga kurun waktu 5 tahun menurut Net Present Value diperoleh Rp 127.174.487,00/tahun, dengan nilai Net B/C 10,63 artinya setiap Rp 1.000 modal akan untung Rp 10.630, dengan titik impas petani berhasil menjual sayuran sebanyak 12,633 kg dan biaya dari investasi akan kembali dalam 1 tahun 9 bulan. Masyarakat Desa Cibodas berada pada tingkat kesiapan 5 yaitu preparation ditandai dengan tersedianya sumber daya lokal dan ketersediaan meluangkan waktu sehingga strategi yaitu membangun pusat pertanian terpadu di kampung cijarekso sebagai pengembangan pusat teknologi 4.0 pemasangan alat pertanian secara komunal sehingga pengeluaran modal sedikit dan membangun koperasi sebagai wadah untuk penjualan hasil panen.